Jesuits and the Early Chinese Catholic Rosary: Unveiling New Insights into the Authorship and Origins of song nianzhu guicheng - Wang, Xintong (Journal of Jesuit studies, 2026)
Song nianzhu guicheng song nian zhu gui cheng (The Method of Reciting the Rosary) is the earliest known illustrated Chinese Catholic work, published in the early seventeenth century. Debates over its authorship, publication date, and place persist in academic circles. While existing studies have productively examined its artistic features and visual adaptation, less attention has been devoted to systematic textual analysis. As a result, key questions about its textual provenance and authorship remain unresolved. This paper seeks to enrich the discourse by conducting a comprehensive comparison of the texts of song nianzhu guicheng, its Portuguese original, and another related Rosary work, in order to shed new light on the text’ s composition and historical context. Three main authorship hypotheses are critically examined: attribution to João da Rocha (luo ru wang, 1565-1623), sole authorship by Gaspar Ferreira (fei qi gui, 1571-1649), or collaborative authorship involving Ferreira and Francisco Furtado (fu fan ji, 1589-1653). Historical evidence seems to contradict Rocha’ s authorship, as his documented work only treated the "Five Sorrowful Mysteries," unlike the fifteen mysteries in song nianzhu guicheng. The case for Ferreira as the sole author is also problematic; close textual analysis suggests his version of the Rosary likely integrated and adapted Rocha’ s earlier work. Drawing on records of missionary activities, this study argues that nianzhu was likely a collaborative work by several missionaries and was first published in Hangzhou between 1620 and 1628.